Content of Hg, Cd, Pb and As in fish species: a review - Julián ZULUAGA RODRÍGUEZ (Universidad de Antioquia, 2015)
Background: One of the main water contaminants are Hg, Cd, Pb and As. The chain of contamination of these metals and metalloid follows a cyclical order: Industry, atmosphere, land, water, phytoplankton, zooplankton, fish, and humans. Currently, Hg, Cd, Pb and As researches are of interest because consumption of fish with high toxic metal and metalloid concentrations affects human health. Objective: Provide information on the characteristics of Hg, Cd, Pb and As in the problematic of fishing resource contamination, their implications on human health, and international evidence on studies conducted on Caranx, Scomberomorus, Epinephelus, Euthynnus, Lutjanus, thunnus and Megalops fish genera. Methods: Database, Science Direct, Pub Med, Escopus, Springer Link, and Scopus, available information was reviewed using the keywords: Heavy metals, water pollution, fish, mercury, cadmium, lead, arsenic, health risk, regulations, biomagnification, and bioaccumulation. Results: The metals that pose the highest risks for human health are mercury, cadmium, lead, and arsenic which cause important complications in the nervous system, kidneys, bones, lungs, and cardiovascular system due to their toxicity and posible carcinogenic effect. Fish contents of Hg, Cd, Pb and As varies depending on the zone, environmental conditions, the contamination level of the fishing site, and the characteristics of the fish, being some fish more prone to accumulating higher concentrations of these metals in their muscles; among the species, the metal that showed the highest risk was mercury, being in high concentrations in the largest, most enduring predatory fish. Conclusions: Studies submitted in this review, may be used as the base for future comparisons with Hg, Cd, Pb and As concentration values in different fish studies for the Caranx, Scomberomorus, Epinephelus, Euthynnus, Lutjanus, and Megalops genera in order to be able to determine consumption recommendations and warnings.